Pengembangan Media Pembelajaran Game Edukasi Ular Tangga untuk Meningkatkan Pemahaman Numerasi Materi Penjumlahan dan Pengurangan - Filahanasari, Eka; Imelda, Imelda; Karmila, Desi (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
This research is motivated by the low value of students in Mathematics, especially addition and subtraction materials. The monotonous learning process, such as lecture methods, repeated practice questions, and the use of simple media such as stones and sticks, are some of the causes. This study aims to describe the media design and produce valid, practical and effective learning media. educational games are used as learning media. This type of research is Research and Development (RnD) with the ADDIE model which includes five stages: Analyze, Design, Development, Implementation, and Evaluation. The first stage of this model is analysis, at this stage the needs of educators and students are analyzed, the characteristics of students are analyzed, and the material is analyzed. The second stage is design, at this stage the CP, teaching modules, instruments and products are designed. Next is the development stage, at this stage it produces a product. Then the implementation stage is product testing, finally the evaluation stage, at this stage it analyzes the research data. The validation results by 3 validators obtained results with Aiken's V criteria, namely the average Valid category. The practicality of the media is high, with a percentage of positive responses from educators of 92% and students of 93% with the Practical category. The effectiveness of the media can be seen from the increase in student learning outcomes through pre-tests and post-tests, with an average N-Gain score of 81.4% with the Effective category. Thus, this learning media is categorized as valid, practical, and effective in improving the understanding of numeracy of grade I students of UPT SDN 07 Sitiung.